Applications of biosensing atomic force microscopy in monitoring drug and nanoparticle delivery. (August 2014) - Lamprecht, Constanze; Hinterdorfer, Peter; Ebner, Andreas
<x xml:space="preserve">Abstract</x> Introduction: The therapeutic effects of medicinal drugs not only depend on their properties, but also on effective transport to the target receptor. Here we highlight recent developments in this discipline and show applications of atomic force microscopy (AFM) that enable us to track the effects of drugs and the effectiveness of nanoparticle delivery at the single molecule level. Areas covered: Physiological AFM imaging enables visualization of topographical changes to cells as a result of drug exposure and allows observation of cellular responses that yield morphological changes. When we upgrade the regular measuring tip to a molecular biosensor, it enables investigation of functional changes at the molecular level via single molecule force spectroscopy. Expert opinion: Biosensing AFM techniques have generated powerful tools to monitor drug delivery in (living) cells. While technical developments in actual AFM methods have simplified measurements at relevant physiological conditions, understanding both the biological and technical background is still a crucial factor. However, due to its potential impact, we expect the number of application-based biosensing AFM techniques to further increase in the near future.